Fixed point theorems of block operator matrices on Banach algebras and an application to functional integral equations. (31st July 2012) - Kaddachi, Najib; Jeribi, Aref; Krichen, Bilel
<x xml:space="preserve">Abstract</x> In this paper, we study some fixed point theorems of a 2 × 2 block operator matrix defined on nonempty bounded closed convex subsets of Banach algebras, where the entries are nonlinear operators. Furthermore, we apply the obtained results to a coupled system of nonlinear equations. Copyright © 2012 John Wiley & Sons, Ltd.